(untitled) (Nigerian Journal of Technology, 2015)
The study addresses the nervous anxiety always noticed in pedestrians as they cross at a 4-arm, Traffic Warden Control intersection in Ilorin metropolis, Nigeria. Two of the approaches (Challenge and Unity) are dualised multilanes while the other two (Obbo and CocaCola) are two-lane non-dualised. The present 4-phase traffic control scheme does not give consideration to pedestrian crossing. The geometric layout and the existing traffic management practice at the intersection were determined and a pedestrian traffic survey was conducted. The critical pedestrian volume of 171 pedestrians/hr was obtained on Challenge approach. Using an average walking speed of 1.2 m/s and a crosswalk width of 3 m a pedestrian crossing time of 787.88 seconds within one hour is obtained as being adequate for the critical approach. A 5-phase scheme is proposed with the fifth phase being an all-stop exclusive phasing for pedestrian movements. Crosswalk should be introduced to concentrate pedestrian crossing activity at a specific location thereby positioning pedestrians to be more visible to traffic wardens and motorists. http://dx.doi.org/10.4314/njt.v35i1.4